Health Expenditures in Mozambique, 2014-2018 - World Bank (World Bank, Washington, DC, 2021)
This brief explores trends in health expenditure and resource allocation in Mozambique between 2014 and 2018. It establishes a baseline for future assessments, with the objective of ensuring that resources continue to shift in alignment with the priorities laid out in the 2017 investment case for reproductive, maternal, newborn, child and adolescent health and nutrition (RMNCAH-N). This analysis can be carried out annually using the data produced by routine information and management systems.